The RNA polymerase II subunit RPB‐9 recruits the integrator complex to terminate Caenorhabditis elegans piRNA transcription. (3rd February 2021) - Berkyurek, Ahmet C; Furlan, Giulia; Lampersberger, Lisa; Beltran, Toni; Weick, Eva‐Maria; Nischwitz, Emily; Cunha Navarro, Isabela; Braukmann, Fabian; Akay, Alper; Price, Jonathan; Butter, Falk; Sarkies, Peter; et al.
Abstract: PIWI‐interacting RNAs (piRNAs) are genome‐encoded small RNAs that regulate germ cell development and maintain germline integrity in many animals. Mature piRNAs engage Piwi Argonaute proteins to silence complementary transcripts, including transposable elements and endogenous genes. piRNA biogenesis mechanisms are diverse and remain poorly understood. Here, we identify the RNA polymerase II (RNA Pol II) core subunit RPB‐9 as required for piRNA‐mediated silencing in the nematode Caenorhabditis elegans . We show that rpb‐9 initiates heritable piRNA‐mediated gene silencing at two DNA transposon families and at a subset of somatic genes in the germline. We provide genetic and biochemical evidence that RPB‐9 is required for piRNA biogenesis by recruiting the Integrator complex at piRNA genes, hence promoting transcriptional termination. We conclude that, as a part of its rapid evolution, the piRNA pathway has co‐opted an ancient machinery for high‐fidelity transcription. Synopsis: The piRNA pathway regulates germ cell development and promotes fertility in animals. The finding that RNA Polymerase II subunit RPB‐9 recruits the Integrator complex to terminate transcription at piRNA genes in C. elegans provides new insight into the mechanisms of piRNA biogenesis. rpb‐9 is required for the generation of mature piRNAs and the initiation of piRNA‐mediated silencing. rpb‐9 is required to repress two DNA transposon families and a subset of somatic genes in the germline. RPB‐9 recruits the Integrator complex at motif‐dependent piRNA loci to terminate transcription of piRNA precursors. Abstract : piRNA biogenesis requires RBP‐9 mediated transcriptional termination at complex piRNA genes.